Improving Lithium-ion Battery Longevity through Predictive Thermal Management - M., Mynavathi; A., Agalya M; J., Hemavaruni; S., Nivetha C; D., Thanya (Journal of Electrical Engineering and Automation, 2025)
Lithium-ion batteries are vital in various storage applications like electric vehicle, renewable energy system and industrial applications. One of the major drawbacks with lithium- ion batteries are overheating. A cost-effective thermal management system is proposed where predictive analysis is employed to reduce thermal stress, thereby increasing reliability and longevity of batteries. Linear regression techniques is employed to forecast temperature fluctuation and activate cooling system when temperature of the lithium-ion battery reaches unsafe limit. The proposed methodology is developed and validated by a low-cost hardware.
Keywords: Lithium-ion Batteries; Thermal Management; Predictive Analytics; Linear Regression; Battery Safety; Real-Time Monitoring